Bisalbuminaemia in pancreatic ascites. Issue 723 (January 1986) - Keidar, S.; Hornstein, L.; Brook, J. G.
Abstract : A patient with pancreatic ascites is described. Electrophoresis of the patient's serum demonstrated bisalbuminaemia, which disappeared after resolution of the ascites.